2017
DOI: 10.1038/s41467-017-00269-1
|View full text |Cite
|
Sign up to set email alerts
|

Activated NK cells cause placental dysfunction and miscarriages in fetal alloimmune thrombocytopenia

Abstract: Miscarriage and intrauterine growth restriction (IUGR) are devastating complications in fetal/neonatal alloimmune thrombocytopenia (FNAIT). We previously reported the mechanisms for bleeding diatheses, but it is unknown whether placental, decidual immune cells or other abnormalities at the maternal–fetal interface contribute to FNAIT. Here we show that maternal immune responses to fetal platelet antigens cause miscarriage and IUGR that are associated with vascular and immune pathologies in murine FNAIT models.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 68 publications
3
71
1
3
Order By: Relevance
“…HLA‐C, HLA‐E and HLA‐G) to generate tolerogenic signals toward the fetus . However, the tolerogenic characteristics of uNK may be disrupted in pregnancies afflicted with infection‐ or alloimmunity‐induced types of inflammation . While maternal obesity associates with elevated inflammation in early pregnancy, our findings suggest that obesity‐associated inflammation may not translate into procytotoxic uNK functions, even though our work shows that obesity correlates with enhanced uNK activity (degranulation) and links with altered NKR expression that is reflective of increased cytotoxicity (i.e.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…HLA‐C, HLA‐E and HLA‐G) to generate tolerogenic signals toward the fetus . However, the tolerogenic characteristics of uNK may be disrupted in pregnancies afflicted with infection‐ or alloimmunity‐induced types of inflammation . While maternal obesity associates with elevated inflammation in early pregnancy, our findings suggest that obesity‐associated inflammation may not translate into procytotoxic uNK functions, even though our work shows that obesity correlates with enhanced uNK activity (degranulation) and links with altered NKR expression that is reflective of increased cytotoxicity (i.e.…”
Section: Discussionmentioning
confidence: 65%
“…While uNK functions are thought to be predominately noncytotoxic, recent studies show that conditions in pregnancy resulting in aberrant inflammation (i.e. infection, alloimmunity) promote uNK‐directed cytotoxicity toward fetal and placental tissue . This suggests the in utero environment is capable of shaping uNK activity and function.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, both decidua basalis and parietalis showed an increased frequency of CD56 + NK cells in women that underwent pre-term labor with acute chorioamnionitis compared to those without chorioamnionitis (134). Although NK cells perform homeostatic roles, under pathological conditions such as fetal alloimmune thrombocytopenia, dNK cells can become activated with prolonged survival, elevated NKp46 and CD107 expression, and perforin release, and can induce trophoblast apoptosis and placental pathology, leading to miscarriage (223).…”
Section: Nk Cellsmentioning
confidence: 99%
“…miR-378 negatively regulates the expression of CD226 in NK cells and CD226 is a target gene of miR-378 NK cells are the body's first line of defense against infections and tumours, and they are also the main effector cells of innate immunity [33]. Abnormal immunity of NK cells is closely related to abortion in pregnant women [34], suggesting that NK cells participate in the regulation of pregnancy. Bioinformatics prediction showed that activated receptor CD226 on the surface of NK cells was a potential target of miR-378 ( Figure 3(A)).…”
Section: Expression Of Mir-378 Is Reduced In Innate Immune Nk Cells Fmentioning
confidence: 99%